2014
DOI: 10.1111/trf.12784
|View full text |Cite
|
Sign up to set email alerts
|

Use of Factor XIII (FXIII) concentrate in patients with congenital FXIII deficiency undergoing surgical procedures

Abstract: BACKGROUND:Patients with congenital Factor XIII (FXIII) deficiency have impaired fibrin stabilization and are at high risk for surgical bleeding. Data regarding the use of FXIII concentrates before and during surgery are lacking. The objective of this study was to report the use of plasma-derived FXIII concentrate (Corifact in the United States; Fibrogammin P in other countries) in patients with congenital FXIII deficiency undergoing surgical procedures. STUDY DESIGN AND METHODS: FXIII concentrate at preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Platelet contractile proteins result in thrombus contraction and increased fibrin density. Furthermore, factor XIII, released by activated platelets, facilitates fibrin cross-linking and increases thrombus stability (Janbain et al 2015). Arterial thrombi have more plasminogen activator inhibitor-1 (PAI-1) (Tynngard et al 2006), which inactivates tPA, allowing less endogenous lysis versus venous thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet contractile proteins result in thrombus contraction and increased fibrin density. Furthermore, factor XIII, released by activated platelets, facilitates fibrin cross-linking and increases thrombus stability (Janbain et al 2015). Arterial thrombi have more plasminogen activator inhibitor-1 (PAI-1) (Tynngard et al 2006), which inactivates tPA, allowing less endogenous lysis versus venous thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report of six patients with congenital FXIII deficiency undergoing surgery covered by pd-FXIII, one patient experienced intraoperative bleeding while another experienced postoperative bleeding despite, in both cases, FXIII activity levels of approximately 0.4 IU/mL. 18 One of these patients, a 53-year-old man undergoing aortic valve replacement, showed fast consumption of pd-FXIII while on cardiopulmonary bypass. The authors concluded that sufficient pd-FXIII should be administered immediately before major surgery to achieve FXIII activity levels exceeding 0.5 IU/mL (1.0 IU/mL in patients undergoing prolonged or complicated surgeries).…”
Section: Surgery In Fxiii Deficiencymentioning
confidence: 97%
“…13 Although FXIII activity as low as 0.03 to 0.1 IU/mL is thought to be sufficient for preventing spontaneous hemorrhages in most patients, 3,5,12,17 bleeding complications have been reported with FXIII activity levels as high as 0.4 IU/mL. 13,18 In terms of diagnosis, it is important to recognize that the results of standard screening tests (e.g., prothrombin time, activated partial thromboplastin time, fibrinogen, and complete blood counts) appear normal in FXIII deficiency. Consequently, the diagnosis requires the performance of specific FXIII activity assays (measuring functional activity, immunological antigen levels, or clot solubility) of variable sensitivity.…”
Section: Fxiii and Congenital Fxiii Deficiencymentioning
confidence: 99%
“…Although all six patients were on regular prophylaxis, an additional preoperative dose of FXIII 25 to 40 U/kg was administered. 60 Postoperative correction dose depended on the surgical procedure and/or on FXIII activity during or after the surgery.…”
Section: Prophylaxis/therapy In Inherited Fxiii Deficiencymentioning
confidence: 99%